Impact of Night Shifts on Health, Attitude, and Social Life of Nursing Students and Staff Nurses at Selected Hospital, Gurugram, Haryana: A Comparative Study - Priya, Sneha; Sarkar, Manidipa; Sharma, Sushmita (Journal of Neonatal Surgery, 2025)
Introduction: Shift work in healthcare, including rotational and fixed night shifts, is essential for providing continuous patient care. However, these irregular work schedules often lead to circadian misalignment, resulting in negative effects on healthcare workers' health and overall quality of life. Nurses working night shifts may experience a range of health issues, such as gastrointestinal problems, sleep disturbances, stress, job strain, and weakened social and familial relationships. This study aims to compare the impact of night shifts on the health, attitude, and social life of nursing students and staff nurses at SGT Hospital, Haryana. Objectives: The study aims to assess and compare the effects of night shifts on the health, attitude, and social life of nursing students and staff nurses in SGT Hospital. Method: A comparative study was conducted at SGT Hospital using a self-structured questionnaire to gather data. The data were analyzed using percentages and frequencies. Design: This research adopts a quantitative approach with a non-experimental comparative descriptive design. Tools and Techniques: The study used socio-demographic data and a self-structured questionnaire to assess the impact of night shifts on physical health, mental health, and psychosocial/social life. A Likert scale was used to evaluate nurses' attitudes toward night shifts. Data were collected via Google Forms from 100 individuals, including 50 nursing students and 50 nursing officers working night shifts, to assess the impact on their health, attitude, and social life. Results: The findings indicate that while nursing students and staff nurses share similar educational backgrounds and face common challenges during night shifts, they significantly differ in terms of age, marital status, and work experience. Both groups experience notable impacts on their physical health, mental well-being, and social life, underscoring the need for targeted interventions to address these challenges.